Unravelling the Potential of Zwitterionic Polymers in Molecular Imprinting - Singh, Meenakshi; Srivastava, Akriti; Mandal, Moumita (Langmuir, 2025)
Molecularly imprinted polymers (MIPs) are a class of molecular receptors that are the closest imitation of biological receptors. They are often called "artificial enzymes". The capability of the MIPs to bind bioactive molecules under specific conditions creates molecular imprinting technology as having considerable potential for customized applications. Polymerization in the presence of a "template" molecule with the assistance of monomers, cross-linkers, and initiators leads to MIPs on extraction of the template molecule from the polymeric matrices. Conventionally neutral monomers were utilized for molecular imprinting. Recently, zwitterionic polymers, having innumerable advantages over nonionic polymers, were realized to be an advantageous choice as a polymeric matrix for imprinting. This review article presents an overview of sulfobetaine, carbobetaine, and phosphobetaine polymers as imprinting matrices for a range of template(s). Zwitterionic polymers are accomplished with biocompatibility, low cytotoxicity, negligible immunogenicity, systematic stability, and long circulation time, and can alleviate quick recognition by the immune system and delayed blood clearance from the body. They can be a fitting candidate for imprinting, especially of biomolecules. The molecular imprinting work on zwitterionic polymers is presented here, which will encourage researchers working in this area.